Detailed investigation of the mixing field and stability of natural gas and propane in highly turbulent planar flames. (1st February 2022) - Elbaz, Ayman M.; Mansour, Mohy S.; Akoush, Bassem M.; Juddoo, Mrinal; Khedr, Alaa M.; Al-Bulqini, Hazem M.; Zayed, Mohamed F.; Ahmed, Mahmoud M.A.; Roberts, William L.; Masri, Assaad R.
Highlights: Combustion process occurs at different mixture inhomogeneity levels. Investigating the mixing field upstream of the reaction zones of inhomogeneous flames is an essential step toward flame stability. Air-to-fuel velocity ratio was the critical parameter affecting the mixture fraction field for the short premixing length. Abstract: In most practical combustion devices, the actual combustion process occurs within different mixture inhomogeneity levels. Investigating the mixture fraction field upstream of the reaction zones of these flames is an essential step toward understanding their structure, stability, and emission formation. In this study, the mixture fraction fields were measured for turbulent non-reacting inhomogeneous mixtures immediately downstream from the slot burner exit, using Rayleigh scattering imaging. The slot burner had two concentric slots. The inner air slot can be recessed at distances upstream from the exit of the outer fuel slot, allowing various degrees of mixture inhomogeneity. Mixture fraction field statistics and the two-dimensional gradient were utilized to characterize the impact of the air-to-fuel velocity ratio, global equivalence ratio, fuel composition, Reynolds number, and the premixing length on the mixture mixing field, and thus flame stability. These impacts were evaluated by tracking the normalized mean mixture fraction and mixture fraction fluctuation transition across the regime diagram for partially premixed flames. The results showed that the air-to-fuel velocity ratio was the critical parameter affecting the mixture fraction field for the short premixing length. Stability results showed that the level of mixture inhomogeneity mainly influenced the flame stability. High flame stability is achieved if a large portion of the inhomogeneous mixture fraction is within the fuel flammability limits.